ARUS PENGELASAN TERHADAP TARIK LASSMAW ELEKTRODA E6013 PADABAJA KARBON RENDAH - Ade Irwan; Muhammad Fitra Ramadhan; Fadly A Kurniawan (Jurnal Simetri Rekayasa, 2020)
This study aims to determine the effect of differences in welding current by performing a Tensile test in order to obtain the values ​​of elastic modulus, strain, reduction and stress. In this study, the material used is the lowest carbon steel with a thickness of 10mm. The welding process is a metallurgical process for binding metal alloy joints which are carried out in a liquid state. From the meaning of this research, it is explained that the notion of welding is a local connection of a metal rod joint where heat energy is used either from the heat source of electricity or a gas burning flame.The material to be examined will be given a variation of welding current of 100Amper, 130 Amper and 160 Amper, which will be welded with a SMAW welding machine using E6013 electrodes with a diameter of 3.2 mm. the method used is the comparative testing method, so that the difference in tensile strength can be found in the three specimens with different welding currents. From the research conducted, the highest tensile strength results were obtained with the number 382.81 MPa on the 130 ampere specimen material. 160 ampere specimen with a yield of 341.94 MPa. And the lowest is a specimen of 100 amperes with a number of 309.28 MPa